SHARING KNOWLEDGE THROUGH OPEN AND DISTANCE E-LEARNING EDUCATION: GLOBALIZING UNIVERSITAS TERBUKA - Mani Festati Broto (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2019)
Universitas Terbuka (UT) as an open and distance e-learning institution in Indonesia, has widely intensify the interconnectivity on international stages. UT adopts international academic standard and pave its vision “to provide access to a world quality higher education for all through open and distance higher education”. Although, most of UT students do not yet have access to adequate internet connection, UT has been a reference for other open education institutions and was acknowledged by the global community to have been succeeded in managing distance education system. By outlining the concept of education diplomacy creates an explanation that the growth of globalized educational collaboration increases the importance of conveying people-to-people engagement through e-learning education system. In previous years, UT has aimed the mission toward an ASEAN distance education collaboration and offer an Open Online Certificate Program through MOOC (Massive Open Online Courses). The aim is to share knowledge among Indonesian and its counterparts in ASEAN.